2005
DOI: 10.1007/s10350-005-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient's Preferences for Adjuvant Postoperative Chemoradiation Therapy in Rectal Cancer

Abstract: This small study demonstrates a substantial variation in patient's preferences with regard to postoperative chemoradiation for rectal cancer. Further studies in the preoperative setting are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The preferences of choosing an adjuvant post-or preoperative therapy have also been the focus of CRC-specific preference studies. Couture et al (2005) found a median point of 5% likelihood of recurrence to choose adjuvant post-operative chemoradiation while Pieterse et al (2007) showed a mean minimum benefit of 4% to undergo PRT. However, the latter authors also found 17% of patients refusing the adjuvant treatment in general; however, subgroup results were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The preferences of choosing an adjuvant post-or preoperative therapy have also been the focus of CRC-specific preference studies. Couture et al (2005) found a median point of 5% likelihood of recurrence to choose adjuvant post-operative chemoradiation while Pieterse et al (2007) showed a mean minimum benefit of 4% to undergo PRT. However, the latter authors also found 17% of patients refusing the adjuvant treatment in general; however, subgroup results were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Couture et al . () found a median point of 5% likelihood of recurrence to choose adjuvant post‐operative chemoradiation while Pieterse et al . () showed a mean minimum benefit of 4% to undergo PRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients’ preferences for chemotherapy in CRC have previously been examined by determining the amount of life cancer patients are willing to forgo to avoid treatment,13 the survival benefit needed to make chemotherapy worthwhile,14 and the recurrence rate at which patients will change their preference from surgery alone to surgery plus chemoradiation 15. Although the strength of patients’ preferences has been explored, less is known about the processes that influence these preferences.…”
Section: Introductionmentioning
confidence: 99%